Comparative Evaluation Of Postoperative Sensitivity Using Total-Etch Versus Self-Etch Bonding Techniques In Resin Composite Restorations: A Randomized Clinical Trial - Marwat, Shahid Ahmad; Maqbool , Hassan; Haq, Umair ul; Rizwan, Zarnab; Sajid, Khadija; Khattak, Shakeel Ur Rehman (Journal of Rawalpindi Medical College, 2024)
Objective: To assess and compare postoperative sensitivity in resin composite restorations using the self-etch versus total-etch technique. Methods: A randomized clinical trial conducted at the Department of Operative Dentistry &Endodontics, from April 1st, 2022, to September 30th, 2022. Patients were assigned to Group A (total-etch) or Group B (self-etch) based on odd or even outpatient department numbers, determined through randomization. Local anaesthesia was administered, following the placement of a rubber dam, a high-speed handpiece with water coolant and an ISO #15 round diamond bur (Shofu. Inc, Kyoto, Japan) used for cavity preparation. In Group A, 37% phosphoric acid etchant (3M, ESPE) was applied for 30 seconds, followed by rinsing and air-drying (triple syringe). Subsequently, the bonding agent (Scotchbond 3M, ESPE) was applied and cured with light. Group B utilized a self-etch priming adhesive (Adper™ 3M) for 20 seconds, followed by exposing the tooth to light for a 20-second curing process. Results: In Group A, the mean and SDs for post-operative sensitivity were 2.48+1.30 VAS at 24 hours and 2.05+1.30 VAS at 2 weeks. Group B showed reduced values of mean and SDs for postoperative sensitivity at 24 hours 1.73+1.66 VAS and 2 weeks 1.25+1.18. Conclusion: Self-etch bonding demonstrated decreased postoperative sensitivity at 24 hours and 2 weeks, suggesting its effectiveness in reducing sensitivity after resin composite restoration. Keywords: Sensitivity, Visual Analog Scale.